1980
DOI: 10.1063/1.439874
|View full text |Cite
|
Sign up to set email alerts
|

Single and double ionization of nitrogen dioxide by electron impact from threshold up to 180 eV

Abstract: Electron impact ionization of nitrogen dioxide has been studied as a function of electron energy up to 180 eV with a double focussing mass spectrometer Varian MAT CH5 and an improved Nier type electron impact ion source. We report the first observation of NO2++ produced via electron impact. Relative partial ionization cross section functions have been obtained for the processes NO2+e→NO2++2e and NO2+e→NO2+++3e. An accurate measurement of the cross section ratio q (NO2++/NO2) /q(NO2+/NO2) has been performed. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1

Year Published

1982
1982
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(13 citation statements)
references
References 16 publications
1
11
1
Order By: Relevance
“…As their data have been normalized using the Ar total cross section of Rapp and Englander-Golden 13 this additional uncertainty is at least Ϯ7%. The partial NO 2 ϩ cross section reported by Stephan et al 19 is approximately a factor of two lower than the present measurements. The overall shape of both cross sections is, however, very similar.…”
Section: Results and Discussion: Nocontrasting
confidence: 78%
See 3 more Smart Citations
“…As their data have been normalized using the Ar total cross section of Rapp and Englander-Golden 13 this additional uncertainty is at least Ϯ7%. The partial NO 2 ϩ cross section reported by Stephan et al 19 is approximately a factor of two lower than the present measurements. The overall shape of both cross sections is, however, very similar.…”
Section: Results and Discussion: Nocontrasting
confidence: 78%
“…The partial cross sections are plotted in Figs. 8-9 together with the previously published NO 2 ϩ cross section of Stephan et al 19 while the total cross section is shown in Fig. 10 together with the calculation of Kim et al 3 The uncertainty in the cross sections presented here is given in the caption to Table II.…”
Section: Results and Discussion: Nomentioning
confidence: 97%
See 2 more Smart Citations
“…II. Also, NO 2 is an unusual molecule in that more NO ϩ ions are produced than NO 2 ϩ ions at low T both by electron-impact ionization 24 and by photoionization. 25 Similar to NH 3 , NO 2 changes its shape upon ionization: The neutral NO 2 is bent while the NO 2 ϩ ion is linear.…”
Section: G Nitrogen Dioxide (No 2 )mentioning
confidence: 99%